2022
DOI: 10.1088/1361-651x/ac5ebc
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the applicability of classical and neural network interatomic potentials for modeling body centered cubic polymorph of magnesium

Abstract: Magnesium (Mg) is one of the most abundant metallic elements in nature and presents attractive mechanical properties in the industry. Particularly, it has a low density and relatively high strength/weight and stiffness/weight ratios, which make it one of the most attractive lightweight metals. However, the huge potential of Mg is restricted by its low ductility, associated with its hexagonal close packed (hcp) structure. This problem can be solved if Mg adopts the body centered cubic (bcc) structure, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Based on these findings the authors concluded that these properties could be improved by specifically targeting bcc structures in the training set. [11] The fact that our potentials reproduce the dynamical as well as elastic properties so well without specifically targeting these values during the training set generation nicely illustrates the ability of our training approach to produce transferable potentials.…”
Section: Phonons and Force Constantsmentioning
confidence: 73%
See 1 more Smart Citation
“…Based on these findings the authors concluded that these properties could be improved by specifically targeting bcc structures in the training set. [11] The fact that our potentials reproduce the dynamical as well as elastic properties so well without specifically targeting these values during the training set generation nicely illustrates the ability of our training approach to produce transferable potentials.…”
Section: Phonons and Force Constantsmentioning
confidence: 73%
“…Our validation results also indicate a significantly better description of bcc Mg, both in the compressed high pressure state as well as at the equilibrium volume, as compared to other recently reviewed Mg potentials. The band structure and density of states for bcc Mg are shown in Appendix C. Troncoso et al [11] review this topic and find MEAM potentials are the best so far to study the dynamical behaviour of bcc Mg, but also report that the same potentials are deficient in their elastic properties. [28] Neural Network Potentials [2,39] reviewed in the same paper are found to be better for this application, but still predict wrong dynamical instabilities or predict them in the wrong part of the band structure.…”
Section: Phonons and Force Constantsmentioning
confidence: 99%